An epidemiological survey of the current status of Zika and the immune interaction between dengue and Zika infection in Southern Taiwan. (April 2020) - Wang, Wen-Hung; Urbina, Aspiro Nayim; Wu, Chia-Ching; Lin, Chih-Yen; Thitithanyanont, Arunee; Assavalapsakul, Wanchai; Lu, Po-Liang; Chen, Yen-Hsu; Wang, Sheng-Fan
Highlights: Data indicated the continuous importation of Zika virus (ZIKV) infection in Taiwan; no indigenous ZIKV infections have been found. Pre-existing convalescent dengue immunity in the Taiwanese population poses a risk for ZIKV infection. The anti-sera from secondary DENV infections was found to promote ZIKV infection via antibody-dependent enhancement (ADE). Abstract: Objectives: This study was performed to examine the current status of Zika and the effects of pre-existing dengue immunity on Zika virus (ZIKV) infection in Southern Taiwan. Methods: A phylogenetic tree was used to analyze the phylogeny of detected ZIKVs. Paired sera from dengue patients were collected for the determination of dengue and Zika infection. Plaque reduction neutralization tests (PRNT) and quantitative reverse transcription PCR (qRT-PCR) were used to determine the titers of neutralizing antibodies and viruses, respectively. An antibody-dependent enhancement (ADE) assay was used to evaluate the effect of anti-dengue antibodies on ZIKV infection. Results: Epidemiological data indicated the continuous importation of ZIKV infection from neighboring Zika epidemic countries into Taiwan. A total of 78 dengue patients were enrolled and 21 paired serum samples were obtained. PRNT90 results for the 21 samples identified eight cases of primary dengue infection and 13 cases of secondary dengue infection; two samples were positive for ZIKV (MR766). Results from the ADE assay indicated that convalescent sera from primary and secondary dengue infection patients displayed significant ADE of the ZIKV infection when compared to healthy controls ( p < 0.05). Conclusions: This study suggests that pre-existing dengue immunity facilitates ZIKV infection and that the continuous importation of ZIKV infection may pose a threat to indigenous Zika emergence in Southern Taiwan.